IslamicGRID and knowledge management - Abdul Wahid, Al-Abrar; Aboubakar Idriss, Hissein; Rameez, Mamdhooh; Salem Almohaifer, Mohammad; Ahmad Dahlan, Abdul Rahman; Dolmoin, Kamarudin; Noordin, Mohamad Fauzan (IIUM Press, 2011)
IslamGRID was developed to collect, preserve, disseminate and promote the knowledge, heritage and beauty of Islam to all Muslims and non-Muslims, whether in the social, political, administrative, industrial and commercial. With the advent of information systems (IS) and information communications technology (ICT), the adoption of Open Innovation Model collaborations as stated by Agensi Innovasi Malaysia in “Innovating Malaysia”, and the increase of the amount of information that Muslim communities and organizations have to deal with, there is a requirement to put strategic process and platform in place to ensure the effective management of Islamic knowledge, experiences, expertise and heritage reaching its target audience. This case study research will look into the content, people, processes and technology and their relationship, which might affect the effectiveness of the IslamGRID portal delivery to the Muslim community (Ummah) as well as to the non-Muslims communities. IslamGRID is proposed to adopt the Quadruple Helix Model collaboration involving Government, Industry, Academia and Citizen -the approach of “we know everything” is history according to AIM. In the initial stage, IslamGRID may involved The application of these areas would be for JAKIM, states (JAIN), Muslims.